1D Chains of Diruthenium Tetracarbonyl Sawhorse Complexes - Fritsch, Nico; Wick, Christian; Waidmann, Thomas; Pflock, Stephan; Dral, Pavlo; Tucher, Johannes; Steiner, Christian; Shubina, Tatyana; Maier, Sabine; Clark, Timothy; Burzlaff, Nicolai (European Journal of Inorganic Chemistry, 2018)
The syntheses of five 1D coordination polymers containing the sawhorse-type unit [Ru-2(mu-OAc)(2)(CO)(4)] linked by various bridging N,N-donor ligands are reported. Various pi-conjugated linkers, such as trans-[1,2-bis(N-methyl)imidazol-2-yl]ethylene (trans-bie), pyrazine (pyz), 4,4-bipyridine (4,4-bipy) and 1,2-bis(4-pyridyl)ethylene (bpe) as well as the aliphatic linker 1,4-diazabicyclo[2.2.2]octane (DABCO), were applied in the syntheses. The formation of 1D coordination polymers was proven by crystal structure determinations of two of the polymeric materials. The geometries and electronic structures of all polymers were analysed further by CASSCF/CASPT2 and DFT calculations based on monomeric model compounds. Finally, first attempts regarding deposition of the 1D chain, the sawhorse fragment and/or the ligands on a highly ordered pyrolytic graphite surface, analysed by STM measurements, are also reported.
Keywords: Coordination polymers; Chain structures; Bridging ligands; N ligands; Ruthenium

Battlement-shaped 1D coordination polymer based on a bis(N-methylimidazole- 2-yl)butadiyne ligand - Waidmann, Thomas; Fritsch, Nico; Tucher, Johannes; Rudolf, Marc; Glaser, Felix; Guldi, Dirk Michael; Burzlaff, Nicolai (Crystengcomm, 2013)
Bis(N-methylimidazole-2-yl)butadiyne (bmib) has been prepared starting from N-methylimidazole following two different pathways. Bmib fluoresces and is capable of forming 1D coordination polymers by clamping together metal units. The molecular structure of a zinc coordination polymer based on bmib and zinc acetate resembles a battlement of a fortress. © 2013 The Royal Society of Chemistry.

Multiply Bonded Metal(II) Acetate (Rhodium, Ruthenium, and Molybdenum) Complexes with the trans-1,2-Bis(N-methylimidazol-2-yl)ethylene Ligand - Fritsch, Nico; Wick, Christian; Waidmann, Thomas; Dral, Pavlo; Tucher, Johannes; Heinemann, Frank Wilhelm; Shubina, Tatyana; Clark, Timothy; Burzlaff, Nicolai (Inorganic Chemistry, 2014)
The synthesis and structural characterization of new coordination polymers with the N,N-donor ligand trans-1,2-bis(N-methylimidazol-2-yl)ethylene (trans-bie) are reported. It was found that the acetate-bridged paddlewheel metal(II) complexes [M-2(O2CCH3)(4)(trans-bie)]n with M = Rh, Ru, Mo, and Cr are linked by the trans-bie ligand to give a one-dimensional alternating chain. The metal-metal multiple bonds were analyzed with density functional theory and CASSCF/CASPT2 calculations (bond orders: Rh, 0.8; Ru, 1.7; Mo, 3.3).